2023
DOI: 10.7759/cureus.42193
|View full text |Cite
|
Sign up to set email alerts
|

Catamenial Pneumothorax in a Patient with Endometriosis: A Case Report

Abstract: Pelvic pain is a common presentation to the emergency department (ED). For female patients, endometriosis can be difficult to diagnose and can have life-threatening complications if missed. In this case report, we present a case of a patient initially presenting to the ED with a few days of crampy lower abdominal pain. After initial imaging, she was found to have a large pelvic hematoma with concern for active extravasation and a large hemothorax. After further evaluation, she was suspected of having endometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…A 38-year-old nulliparous who had an ovarian cyst as a teenager and right pneumothorax at age 35 that was managed by wedge resection, pleurodesis, and diaphragm plication presented intense lower abdominal pain beginning a soon after the menstrual period 9 . Imaging studies revealed a pelvic hematoma in the right adnexal area and large hyperdense right pleural effusion, suggesting passage of blood by diaphragmatic defect 9 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A 38-year-old nulliparous who had an ovarian cyst as a teenager and right pneumothorax at age 35 that was managed by wedge resection, pleurodesis, and diaphragm plication presented intense lower abdominal pain beginning a soon after the menstrual period 9 . Imaging studies revealed a pelvic hematoma in the right adnexal area and large hyperdense right pleural effusion, suggesting passage of blood by diaphragmatic defect 9 .…”
mentioning
confidence: 99%
“…A 38-year-old nulliparous who had an ovarian cyst as a teenager and right pneumothorax at age 35 that was managed by wedge resection, pleurodesis, and diaphragm plication presented intense lower abdominal pain beginning a soon after the menstrual period 9 . Imaging studies revealed a pelvic hematoma in the right adnexal area and large hyperdense right pleural effusion, suggesting passage of blood by diaphragmatic defect 9 . She underwent a laparoscopy which showed approximately one liter of dark red blood and clots in the abdominal cavity, the uterus and adnexa adhered to the colon and pelvic wall, besides lesions resembling endometriosis disseminated throughout the abdomen 9 .…”
mentioning
confidence: 99%
See 1 more Smart Citation